2014
DOI: 10.1007/s10661-014-4113-y
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrients and trace metals in soil and food crops of Isfahan Province, Iran

Abstract: The distribution of 10 macronutrients and trace metals in the arable soils of Isfahan Province, their phytoavailability, and associated health risks were investigated; 134 plant and 114 soil samples (from 114 crop fields) were collected and analyzed at harvesting time. Calculation of the soil pollution index (SPI) revealed that arable soil polluted by metals was more severe in the north and southwest of the study area. The results of cluster analysis indicated that Pb, Zn, and Cu share a similar origin from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 51 publications
5
9
0
1
Order By: Relevance
“…It was interesting also to advise that our soils have higher levels of P, probably by the widespread use of sulfate and phosphate fertilizers as indicated by Keshavarzi al. for Iranian soils [44] that can reinforce the origin of Cr and Ni in our soils.…”
Section: Soil Physicochemical Properties and Pte Levels In Studied Soilssupporting
confidence: 73%
See 1 more Smart Citation
“…It was interesting also to advise that our soils have higher levels of P, probably by the widespread use of sulfate and phosphate fertilizers as indicated by Keshavarzi al. for Iranian soils [44] that can reinforce the origin of Cr and Ni in our soils.…”
Section: Soil Physicochemical Properties and Pte Levels In Studied Soilssupporting
confidence: 73%
“…The PTE levels obtained in this studied were compared with data reported by other studies carried out for agricultural soils in Iran (Table 2). When compared with the results of previous studies in Iran e.g., [13,40,41,[43][44][45][46][47], average values are similar or lower to indicate by them, probably due to some of these studies were carried out near to industrial areas e.g., [40,41]. Results showed significant enrichment of Cr and Ni in studied agricultural lands, although with similar values as indicated by Doabi et al [13] for agricultural areas in Kermanshah province, Western Iran.…”
Section: Soil Physicochemical Properties and Pte Levels In Studied Soilssupporting
confidence: 69%
“…By contrast, the results of a long-term field experiment showed that as the SOM contents increased, there were decreases in the mobility of Cu, Fe, and Mn in the soil solution, whereas that of Zn increased [ 6 ]. The mechanisms responsible for these effects were not investigated [ 19 ], but the variability may be due to the strong buffering capacity of the soil, or the micronutrient levels may depend on soil characteristics, including the pH, texture, organic matter, redox conditions [ 35 ], and the type and quantity of oxyhydroxides present, as well as the crop species considered [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The average concentrations of the micronutrients or heavy metals were averaged over the two experimental years under the same treatment. The daily intake (DI i ) of elements was calculated by: DI i = C i ×Q, where C i is the concentration of element i in the crop (mg kg −1 ) and Q is the daily consumption of the crop in the experimental area (kg day −1 ) [ 35 ]. The per capita consumption of wheat grain by Chinese inhabitants is 0.2 kg day −1 [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of land types, cultivated land, which is intimately associate with human activity, has received significant attention. However, most investigation has focused on common crops, such as wheat and corn [9][10] , and their relationship with PTEs in cultivated soil [11] , and it has been found that the potentially toxic element (PTE) pollution of certain crops is positively correlated with that of the soil, either directly or by promoting contaminant uptake [12] . Wolfberry (Lycium barbarum L.) is a plant belonging to the Lycium genus of the Solanaceae family.…”
mentioning
confidence: 99%